Is oxidative stress - antioxidants imbalance the physiopathogenic core in pediatric obesity? - Lupu, Ancuta; Fotea, Silvia; Jechel, Elena; Starcea, Iuliana Magdalena; Ioniuc, Ileana; Knieling, Anton; Salaru, Delia Lidia; Sasaran, Maria Oana; Cirstea, Olga; Revenco, Ninel; Mihai, Cristina Maria; Lupu, Vasile Valeriu; et al. (Frontiers in Immunology, 2024)
Despite the early recognition of obesity as an epidemic with global implications, research on its pathogenesis and therapeutic approach is still on the rise. The literature of the 21st century records an excess weight found in up to 1/3 of children. Both the determining factors and its systemic effects are multiple and variable. Regarding its involvement in the potentiation of cardio-vascular, pulmonary, digestive, metabolic, neuro-psychic or even dermatological diseases, the information is already broadly outlined. The connection between the underlying disease and the associated comorbidities seems to be partially attributable to oxidative stress. In addition to these, and in the light of the recent COVID-19 pandemic, the role played by oxidative stress in the induction, maintenance and potentiation of chronic inflammation among overweight children and adolescents becomes a topic of interest again. Thus, this review's purpose is to update general data on obesity, with an emphasis on the physiopathological mechanisms that underlie it and involve oxidative stress. At the same time, we briefly present the latest principles of pathology diagnosis and management. Among these, we will mainly emphasize the impact played by endogenous and exogenous antioxidants in the evolutionary course of pediatric obesity. In order to achieve our objectives, we will refer to the most recent studies published in the specialized literature.